A STUDY ON NEW HIRING STRATEGIES TO MANAGE TALENT CRISIS AT ENTRY LEVEL FROM THE PERSPECTIVE OF RECRUITERS AND FRESH GRADUATE ENGINEERJOB SEEKERS - Rehman, Sufia; Mazhar, S.Shahid (International Journal of Research -GRANTHAALAYAH, 2016)
Internet apart from influencing life of people has also emerged as a key HR tool for acquiring talent. Traditional HR strategies are being modernized, driven by technology and innovations. The remarkable popularity of internet & Social Media Sites, lower hiring cost & res ponce time and competitive advantage has allured the recruiters not only to use it for effective branding but also for hiring. They offer a great source of talent pool, as almost every fresh graduate / professional has Social Media account. Professional networking with social media as a recruitment tool is influencing with offer of better platform to both recruiters and this study discusses the Impact & effectiveness of New Hiring Strategies. Their advantages and limitations over traditional methods and their role in making or breaking the job opportunity. The study used data from secondary sources also personal interviews with industry professionals and Job seekers were conducted. A comprehensive analysis of the new trends has been done and described through various graphs and diagrams. The findings of the survey show a significant change in trend from traditional recruitment methods to modern techniques. However there remains good scope for improvement in utilizing the various benefits of the new strategies